EXTERNAL MAGNETIC FIELD IN CHIRAL MODEL OF GRAPHENE - Y. P. YBAKOV; A. B. AHMED; J. SAMBO; M .ABDULKADIR, (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY (2536-6041), 2019)
The simplest scalar chiral model of graphene suggested earlier and based on the SU (2) order parameter is generalized by including 8-spinor field as an additional order parameter for the description of spin (magnetic) excitation in graphene. As an illustration the interaction of the graphene layer with the external magnetic field was studied and the result showed the weakening of the field inside the graphene.